FEATURES OF ORGANIZING ACCOUNTING AND CONTROL OF PUBLIC PROCUREMENT IN BUDGETARY INSTITUTIONS UNDER SUSTAINABLE DEVELOPMENT CONDITIONS - SHYNKARENKO, Olha; KOZHUSHKO, Olga; KUMANENKO, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the features of organizing accounting and control of public procurement in budgetary institutions under conditions of sustainable development. Public procurement is considered as a key instrument of public financial management that ensures the fulfillment of state and local government functions, efficient allocation of budgetary resources, and delivery of public goods and services. The economic essence of public procurement and its role in enhancing transparency, accountability, and financial discipline in the public sector are substantiated.Special attention is paid to the regulatory and legal framework governing procurement activities in Ukraine, including recent transformations related to digitalization, the introduction of the electronic procurement system Prozorro, and the functioning of procurement under martial law. The study identifies the specific features of accounting for public procurement transactions at various stages of the procurement cycle, including planning, contracting, execution, and reporting. The close interconnection between accounting procedures and the budget process, as well as their importance for ensuring the legality and effectiveness of expenditures, is emphasized.The article analyzes the system of internal and external control of public procurement in budgetary institutions, highlighting its role in preventing violations, minimizing corruption risks, and improving the efficiency of budget funds utilization. Internal control mechanisms, external state financial control, and public oversight are examined as complementary components of an integrated control system. Particular attention is given to risk-oriented approaches and the use of information and analytical tools based on open data from electronic procurement platforms.The expediency of integrating accounting and control procedures with electronic procurement systems is substantiated as a prerequisite for increasing transparency, reducing duplication of information, and strengthening accountability. The study argues that, in the context of sustainable development, accounting and control of public procurement should not be limited to compliance with legal requirements but should also focus on assessing long-term economic, social, and environmental effects.The proposed directions for improving accounting and control support of public procurement are aimed at enhancing the efficiency of budgetary resource management, strengthening internal control, and aligning procurement practices with the principles of transparency, efficiency, and sustainable development.
Keywords: public procurement; budgetary institutions; accounting; control; sustainable development; internal control